Heart rate variability as a biomarker of self-control and its relationship with depression - Darwin, Marielle L., author; Davalos, Deana, advisor; Thomas, Michael, committee member; Rickard, Kathryn, committee member; Tracy, Brian, committee member (Colorado State University. Libraries, 2021)
Human behavior is guided by a desire to attain certain goals. Individuals must manipulate the pursuit of multiple goals simultaneously and decide how to navigate their environments to support the desires they most value. Failures of self-control are common and present as psychopathologies characterized by emotional and cognitive dysregulation, namely depression. The relationship between poor self-control and the manifestation of depression is critical to target in order to better predict, understand, diagnose, and treat symptomologies, yet the precise nature of the relationship between self-control and depression is insufficiently understood. The current study employed a novel approach to investigate the relationship between self-control and depression and whether our understanding of that relationship could be improved with the incorporation of heart rate variability (HRV), a robust neurocardiac biomarker of self-control-related abilities. Findings supported the merit of HRV as a biomarker of self-control and revealed that self-control fully mediated the relationship between HRV and depression, although effect sizes indicate that the relationships were weak. It was expected that age played a role in this relationship due to the changing lifespan trajectories of neurocardiac networks interconnected with self-control and depression, although this premise was found to be unsupported. These discoveries deepen our understanding of the neurocognitive and autonomic dynamics of depression and supplicate clinical researchers aiming to decrease dysfunction to entertain approaches supported by a biopsychological perspective.
Keywords: biomarker; self-control; depression; heart rate variability